KEEFEKTIFAN PEMBELAJARAN BERDIFERENSIASI TERHADAP HASIL BELAJAR BAHASA INDONESIA SISWA KELAS III SDN 1 PAKALU I - Endah Lestari, Putri; Rahman Rahim, Abdul; Bahri, Aliem (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The main problem of this research is to determine the effectiveness of differentiated learning on Indonesian language learning outcomes for third-grade students at SDN 1 Pakalu I. This study aims to investigate the effectiveness of differentiated learning on Indonesian language learning outcomes for third-grade students at SDN 1 Pakalu I in classes that use differentiated learning and those that do not, as well as to determine whether there are differences in Indonesian language learning outcomes among third-grade students at SDN 1 Pakalu I. This study uses a quasi-experimental research method. The population of this study consists of all third-grade students at SDN 1 Pakalu I. The sampling technique used is total sampling or saturated sampling. The instrument used is a test instrument in the form of multiple-choice questions to measure student learning outcomes with a Pre-Test Post-Test Control Group Design. Based on the research findings, the Indonesian language learning outcomes of students in the experimental class that used differentiated learning showed 94% in the category of mastery learning and 6% in the category of not mastering. The level of Indonesian language learning outcomes in the control class that did not use differentiated learning showed 50% mastery learning and 50% not mastering. The hypothesis test results obtained a sig (2-tailed) of 0.000, meaning H0 is rejected (0.000 < 0.05). H1 is accepted because sig (tailed) > α or (0.166 > 0.05). In the T-test analysis, sig > t-table or (4.742 > 2.036). The hypothesis testing concludes that there is a significant difference in learning outcomes between students in the experimental class using the differentiated learning approach and the control class using conventional learning models in Indonesian language learning at SDN 1 Pakalu I.